On a class of piecewise continuous Lyapunov functions and eventual stability for nonlinear impulsive Caputo fractional differential equations via new generalized Dini derivative - Ante, J.E.; Essang, S.O.; Atsu, J.U.; Ekpenyong, E.O.; Effiong, R. D. (International Journal of Mathematical Analysis and Modelling, 2025)
In this paper, the eventual stability for nonlinear impulsive Caputo fractional differential equations with fixed moments of impulse is examined using the vector Lyapunov functions which is generalized by a class of piecewise continuous Lyapunov functions. Together with the comparison results, sufficient conditions for the eventual stability of impulsive Caputo fractional differential equations are presented. Results obtained are extension and improvements on the existing results.